ORGANIZATION OF STUDENTS’ INDEPENDENT WORK THROUGH THE ACTIVE USE OF DISTANCE LEARNING TECHNOLOGIES IN TECHNICAL UNIVERSITIES - Kalyanova, Ludmila (Revista Inclusiones, 2020)
The article discusses the reasons for increasing the role of independent work of students on educational material and strengthening the responsibility of teachers for its successful implementation, as well as the principles of successful organization of students’ independent work are distinguished. Special attention is paid to the degree of efficiency and expediency of use of such creative task as the abstract in the educational system in modern conditions of Internet availability of any information. The organization of independent work of students is carried out through the active use of distance learning technologies implemented through the open information and educational environment of the University. Under such conditions the effectiveness of its organization determines the quality of the entire educational process and the formation of professional competencies.